Overconfidence, Overreaction and Personality - Durand, Robert; Newby, R.; Tant, K.; Trepongkaruna, S. (Emerald Group Publishing Ltd., 2013)
Purpose – The purpose of this paper is to systematically profile investors’ personality traits toexamine if, and how, those traits are associated with phenomena observed in financial markets. Inparticular, the paper looks at overconfidence and overreaction in an experimental foreign exchangemarket.Design/methodology/approach – The paper measures the personality of the subjects using theshort form of the NEO-PIR instrument, the NEO-FFI developed by Costa and McRae (1992) which is based on Norman’s (1963) “Big Five” personality constructs of negative emotion, extraversion,openness to experience, agreeableness and conscientiousness. The paper measures psychological gender using questions developed by Bem (1994). Preference for innovation and risk-taking propensity are measured using instruments developed by Jackson (1976). The paper then examines the behavior of the subject who traded interactively in “real time” in an interactive-simulated foreign exchange market where “price discovery” was instantaneous and pricing decisions were made instantaneously as items of news, determined by the researchers, were released.Findings – The paper demonstrates that personality traits are associated with overconfidence andoverreaction in financial markets. The paper presents meta-analysis which facilitates the development of a posteriori theories of how particular traits affect investment; there are important roles for risktaking propensity, negative emotion, extraversion, masculinity, preference for innovation andconscientiousness.Originality/value – A typical behavioral finance paper might find an empirical regularity in pricesand, on the basis of such patterns, infer the underlying psychology motivating the behaviorof investors. The approach differs from this caricature of the “typical” behavioral finance paper.The paper does not infer the underlying psychology of investors from patterns in prices. Rather, thepaper learns about investors by systematically profiling their personality traits. The paper thendemonstrates how those traits are associated with the prices generated by the investors the authorsstudy. In focussing on the role of individual personality, the paper refocusses behavioral finance on the individuals who set prices.